An Investigation of video tutorial criteria for studio lighting course / Mohamad Zaidi Sulaiman and Mohd Nasiruddin Abdul Aziz - Mohamad Zaidi, Sulaiman; Mohd Nasiruddin, Abdul Aziz (Universiti Teknologi MARA, Perak, 2017)
E-learning has been identified as one of the most relevance method in teaching and learning process, especially through the video tutorial materials. This research aims to investigate the most effective criteria of contemporary video tutorial that been used for studio lighting course in photography education. The studio lighting subject was selected as the research subject due to the lack of understanding among the students during the preliminary study. Mixed method approach been used to gather all the related data in this investigation including contextual analysis of literature review, questionnaires survey, and expert interviews. The finding of this research focusing on video tutorial criteria’s; Typography and text, video duration, the language, lighting condition, audio and narrator, instructor, graphic elements, various shot, and equipment support.